Corrigendum to “Inhibition of Key Digestive Enzymes Related to Diabetes and Hyperlipidemia and Protection of Liver-Kidney Functions by Trigonelline in Diabetic Rats” [Sci Pharm. 2013; 81: 233–246] - Hamden, Khaled (Österreichische Apotheker-Verlagsgesellschaft, 2014)
This is a corrigendum to the article ‘Inhibition of Key Digestive Enzymes Related to Diabetes and Hyperlipidemia and Protection of Liver-Kidney Functions by Trigonelline in Diabetic Rats’ [Sci Pharm. 2013; 81: 233–246]. Figure 6 is replaced.